If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x(x + -1) = 56 + -11x Reorder the terms: 6x(-1 + x) = 56 + -11x (-1 * 6x + x * 6x) = 56 + -11x (-6x + 6x2) = 56 + -11x Solving -6x + 6x2 = 56 + -11x Solving for variable 'x'. Reorder the terms: -56 + -6x + 11x + 6x2 = 56 + -11x + -56 + 11x Combine like terms: -6x + 11x = 5x -56 + 5x + 6x2 = 56 + -11x + -56 + 11x Reorder the terms: -56 + 5x + 6x2 = 56 + -56 + -11x + 11x Combine like terms: 56 + -56 = 0 -56 + 5x + 6x2 = 0 + -11x + 11x -56 + 5x + 6x2 = -11x + 11x Combine like terms: -11x + 11x = 0 -56 + 5x + 6x2 = 0 Factor a trinomial. (-7 + -2x)(8 + -3x) = 0Subproblem 1
Set the factor '(-7 + -2x)' equal to zero and attempt to solve: Simplifying -7 + -2x = 0 Solving -7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -2x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = 0 + 7 -2x = 0 + 7 Combine like terms: 0 + 7 = 7 -2x = 7 Divide each side by '-2'. x = -3.5 Simplifying x = -3.5Subproblem 2
Set the factor '(8 + -3x)' equal to zero and attempt to solve: Simplifying 8 + -3x = 0 Solving 8 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = 0 + -8 -3x = 0 + -8 Combine like terms: 0 + -8 = -8 -3x = -8 Divide each side by '-3'. x = 2.666666667 Simplifying x = 2.666666667Solution
x = {-3.5, 2.666666667}
| 34+ds+4-4ds-9876655= | | 12-t=5t | | 34xds+4-4ds-9876655= | | 4(y+5)+4=60 | | 0.67x+1.33=-0.67 | | 5-(x/3)=7 | | 9d-d+4d+6-4d=0 | | 1x-1=5x+3x-8 | | -3z+8+(-12z)=-2 | | 5x+12+x+3x-2=180 | | d+r= | | 2k+5/3+8/3=1/3 | | -3z+8+(-12z)=-12 | | 4x^2-2x+7=0 | | 2x+7=18-20x | | 5g+4(-5+3g)=-1-g | | 2.65=1.8b+3-2.5b | | 2x+5=10x-5 | | .6*x=10 | | 2k+5/3+2/2/3=1/3 | | 2x+4(x-5)=11 | | -0.9b-1.64b=2.794 | | -2.3+0.7x=1+0.6x-1.8x-6.53 | | 5x+5=2x-3 | | -1v+1=-2v+4 | | 15x-4y=6 | | -2.3+0.7x=1+0.6-1.8x-6.53 | | (7+6)2= | | 4x-4+1=21 | | -2.9x-1.5=5.1848+0.3x | | 4(x-4)=40-4x | | y+7=56 |